2017
DOI: 10.1111/jcmm.13107
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of Araloside C against myocardial ischaemia/reperfusion injury: potential involvement of heat shock protein 90

Abstract: The present study was designed to investigate whether Araloside C, one of the major triterpenoid compounds isolated from Aralia elata known to be cardioprotective, can improve heart function following ischaemia/reperfusion (I/R) injury and elucidate its underlying mechanisms. We observed that Araloside C concentration‐dependently improved cardiac function and depressed oxidative stress induced by I/R. Similar protection was confirmed in isolated cardiomyocytes characterized by maintaining Ca2+ transients and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 40 publications
2
21
0
1
Order By: Relevance
“…We first detected the effects of AsC on HSP90 expression levels in H/R-treated H9c2 cardiomyocytes. Consistent with our previous reports ( Wang et al, 2017a ), AsC treatment significantly inhibited the H/R-induced down-regulation of HSP90 expression ( Figures 6A,B ).…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…We first detected the effects of AsC on HSP90 expression levels in H/R-treated H9c2 cardiomyocytes. Consistent with our previous reports ( Wang et al, 2017a ), AsC treatment significantly inhibited the H/R-induced down-regulation of HSP90 expression ( Figures 6A,B ).…”
Section: Resultssupporting
confidence: 93%
“…A growing body of evidence implicates that HSP90 plays a critical role in the protective effect of myocardial ischemic preconditioning ( Jiao et al, 2008 ; Amour et al, 2009 ) and against I/R injury ( Kupatt et al, 2004 ; Zhu et al, 2016 ). Our oratory previously revealed that AsC was able to bind to the HSP90 protein in vitro in a dose-dependent manner with the KD 29 μM ( Wang et al, 2017a ).The current results confirmed that AsC significantly attenuated the apoptosis and the down-regulation of HSP90 expression induced by H/R H9c2 cardiomyocytes. By contrast, inhibition of HSP90 by 17-AAG, a well-known inhibitor of HSP90, notably blocked the AsC-induced cardioprotective effect against H/R injury ( Figures 6C – E ).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The total saponins extracted from AS, which are found to be the main pharmacological active ingredients of AS, have been proved to exhibit anti-myocardial ischemic, anti-hypoxic activities, anti-oxidative as well as anti-inflammatory and anti-apoptotic capacity (Wang et al, 2003 ; Lee et al, 2009 ). We previously demonstrated that triterpenoid saponin Elatoside C and Araloside C from AS could protect the myocardial cells from ischaemia/reperfusion (IR) injury and reduce I/R-induced oxidative stress and apoptosis in cardiomyocytes (Wang et al, 2014b , 2015 , 2017 ). We also reported that the proteomic profiling of CE targets associated with anti-apoptosis effect in endothelia cells (Tian et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%